Aluminum-Catalyzed Cross Selective C3–N1′ Coupling Reactions of N-Methoxyindoles with Indoles - Keisuke Tokushige; Toshiki Yamashiro; Seiya Hirao; Takumi Abe (Chemistry, 2023)
C3–N1′ bond formation of bisindoles has been a great challenge due to the intrinsic reactivity of indoles as both C3 and N1-nucleophilic character. Herein, we demonstrate an C3–N1′ cross-coupling reaction of indoles using N-methoxyindoles as N-electrophilic indole reagents in the presence of Lewis acid. The bisindoles generated in this transformation are latent C3-nucleophile, allowing them to be used as strategic intermediates in sequential C3–N1′–C3′–N1″ triindole formations. The potential synthetic usefulness of this sequential transformation was highlighted upon application to the construction of C3–N1 looped polyindoles.